2018
DOI: 10.1016/j.addbeh.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial testing of the brief adolescent smoking curiosity scale (ASCOS)

Abstract: ASCOS presented good psychometric properties and passed initial validity-testing through associations with antecedents of smoking. ASCOS was a better predictor of susceptibility to smoke than did a traditional single-item measure used by previous research. As an implication, ASCOS can be crucial to the development of tailored interventions for smoking prevention that can reduce smoking curiosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
4
12
0
Order By: Relevance
“…Based on the theory of development, adolescence is characterized by an elevation in curiosity towards various objects as it is a cognitive development stage, enhancing the need to explore new activities, including smoking. Furthermore, curiosity is identified as a person's internal motivational system, activated by specific stimuli or activities, which contain uncertainty and novelty, and further motivates exploratory behavior [55]. This study showed inquisitiveness to be a major factor contributing to the risk of smoking among adolescents in Aceh, therefore, supporting previous studies that reported a close relationship between seeking a sensation and cigarette use.…”
Section: Discussionsupporting
confidence: 85%
“…Based on the theory of development, adolescence is characterized by an elevation in curiosity towards various objects as it is a cognitive development stage, enhancing the need to explore new activities, including smoking. Furthermore, curiosity is identified as a person's internal motivational system, activated by specific stimuli or activities, which contain uncertainty and novelty, and further motivates exploratory behavior [55]. This study showed inquisitiveness to be a major factor contributing to the risk of smoking among adolescents in Aceh, therefore, supporting previous studies that reported a close relationship between seeking a sensation and cigarette use.…”
Section: Discussionsupporting
confidence: 85%
“…Based on the theory of development, adolescence is characterized by an increase in curiosity about various objects, because it is a stage of cognitive development, enhancing the need to explore new activities, including smoking. Furthermore, curiosity is identified as a person's internal motivational system, activated by specific stimuli or activities, which involve uncertainty and novelty and further motivate exploratory behavior [56]. This study showed inquisitiveness to be a major factor contributing to the risk of smoking among adolescents in Aceh, supporting previous studies that reported a close relationship between seeking a sensation and cigarette use.…”
Section: Discussionsupporting
confidence: 84%
“…Based on the theory of development, adolescence is characterized by an increase in curiosity about various objects, because it is a stage of cognitive development, enhancing the need to explore new activities, including smoking. Furthermore, curiosity is identi ed as a person's internal motivational system, activated by speci c stimuli or activities, which involve uncertainty and novelty and further motivate exploratory behavior [54]. This study showed inquisitiveness to be a major factor contributing to the risk of smoking among adolescents in Aceh, supporting previous studies that reported a close relationship between seeking a sensation and cigarette use.…”
Section: Discussionsupporting
confidence: 84%